30th AIAA Applied Aerodynamics Conference 2012
DOI: 10.2514/6.2012-3229
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Wind Tunnel Wall Interference on Two-dimensional Airfoil by New Porous Wall Model

Abstract: To analyze wall interference of a transonic wind tunnel, flows of two-dimensional airfoil with wind tunnel porous walls are computed by CFD and the new porous wall model. First, the computational results are validated by comparing with measurement. The porous wall model shows high accuracy enough to precisely simulate the wall interference. Effect of the wall interference is discussed by comparing two kinds of computational results with and without the wind tunnel wall. Wall interference by the porous wall is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…An advantage of the present method is that the interference quantity on the wing chord can be specified where there is no CFD solution. Although previous research showed that the wall interference quantity computed by the linearized potential equation has some error in transonic flow cases, 7) its accuracy is sufficient for the present qualitative discussion. In the present study, Eqs.…”
Section: Evaluation Of Interference Quantitymentioning
confidence: 75%
See 1 more Smart Citation
“…An advantage of the present method is that the interference quantity on the wing chord can be specified where there is no CFD solution. Although previous research showed that the wall interference quantity computed by the linearized potential equation has some error in transonic flow cases, 7) its accuracy is sufficient for the present qualitative discussion. In the present study, Eqs.…”
Section: Evaluation Of Interference Quantitymentioning
confidence: 75%
“…In our previous study, we investigated how to change the flow field of a two-dimensional airfoil by wall interference and showed the wall interference reduced the Mach number and flow angle. 7) Also in the present study, the interference values for the Mach number and flow angle are computed, and we investigate the wall interference effect in the three-dimensional flow field. Then, in order to understand the wall interference in more detail, the effect on the lambda shock and aerodynamics coefficients are discussed in terms of the interference values of Mach number and flow angle.…”
Section: )mentioning
confidence: 99%